THE USE OF ARTIFICIAL INTELLIGENCE TO CONTROL CYBER CRIMES IN INDIA : AN OVERVIEW - Singh, Rang Nath (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The term Artificial intelligence (AI) is prominent in the today's world of technology. In so many ways, it is still a developing science in light of the problems presented by the twenty-first century. AI use has been established in daily life. Since AI has such a significant influence on human existence now, it is difficult to comprehend a world without it. Simply define, artificial intelligence (AI) is the study of how people think, work, learn, and decide in every situation in life, whether it is connected to problem-solving, learning something new, thinking logically, or coming up with a solution, etc. Cybercrimes are becoming pretty common and frequently reported in the news. It is a global challenge, not simply one that affects one nation. AI is meaningless without strong security measures since it may be readily accessible by outsiders. Governments, banks, and global corporations now face a serious threat as a result of cyber security threats. Hackers use a lot of private and business data to their advantage.